Expert Opinion on Wetboek van Strafrecht Art 263, 264, 266 (Criminal Code) Versus Use of Birth Certificates in Petition for Cassation Number 3561 K/Pdt/2020. 05 August 2020. Juncto Determination of the Central Jakarta District Court Number 36/Pdt.P/2020. - Youngky Fernando (Fakultas Hukum, Universitas Warmadewa, 2023)
Whereas on February 3, 2020, there was a Central Jakarta District Court Decision. Class-1-A-Special, Decision on the Application for Determination Number 36/Pdt.P/2020.